A Voice Data Storage Strategy of Record Server in Broadband Cluster System - Chunbin Dou; Zhihui Xiao; Yishan Chen (Dianxin kexue)
With the rapid development of wireless high-speed data services，broadband has become an inexorable trend of the development of wireless network. In the process of cluster communication system for command and control，the system will provide data on the direction of broadband and business diversification. Based on the characteristics of the broadband cluster system，the needs of the recording server were analyzed，and a store strategy was proposed，where various quarter session data was received by multi-threaded and stored in the cache. Then， according to the session category，the session data was stored in the disks in document form，using hierarchical directory management method，in order to provide a convenience query and playback for client.